Improving Students’ Skill in Writting Essay by Using Substitution Drill at The Eight Grades of SMP PAB 2 HELVETIA - Priscilla, Nathasya; Harahap, Dina Iramayanti (Edumaspul: Jurnal Pendidikan, 2025)
This study was done to help eighth-grade students at SMP PAB 2 Helvetia improve their writing skills by using substitution drills that focus on the simple present tense. The research started because many students had trouble making sentences with correct grammar and organizing their thoughts clearly when writing essays.The main purpose of this investigation was to determine whether the application of substitution drills could positively influence students’ writing performance. The subjects of the research were 32 eighth-grade students in the 2025 academic year. Data were collected through writing assessments, observation sheets, and field notes. The results showed that students' writing skills improved a lot after using substitution drills.In the first cycle, 56.25% of students reached the minimum passing standard, and this figure rose to 84.37% in the second cycle. The observed improvement encompassed various components, including grammar accuracy, sentence organization, vocabulary mastery, and textual coherence in essay writing.In conclusion,using substitution drills in teaching the simple present tense helped improve students' ability to write essays. Because of this, it is recommended as a useful and effective way to help students get better at writing English compositions